Analysis of the Republic of Armenia’s foreign trade at the framework of EAEU - Hayrapetyan, Grigor (Bulletin of Yerevan University G: Economics, 2023)
Over the past two decades, the role and importance of regional economic integration groupings in the world economy has increased. Starting from 2015 the Republic of Armenia is a member of the EAEU and applies the common customs tariffs of the EAEU in foreign trade. In the article the features of Armenia's foreign trade in general and within the framework of the EAEU are presented. In particular, it was substantiated that the application of the common customs tariffs of the EAEU would contribute to the development of local production in Armenia, the need for cooperation between companies of the EAEU member countries was emphasized, and it was also revealed that the Republic of Armenia exports products to the EAEU countries with greater added value than to other countries and regions. Liberalization of the services market within the EAEU can create additional opportunities for the development of the RA’s economy, since international trade in services in the RA is quite developed, this will increase competitiveness of the service sector in the RA. The analysis revealed that, despite all the difficulties, the foreign trade of the Republic of Armenia with the EAEU countries is developing, and membership in the EAEU can ensure stable economic growth of the RA economy in the long term.
Keywords: export; import; international trade; internationals trade in services; EAEU; trade balance; regional economic integration